HUBUNGAN PENGETAHUAN TENTANG PENDEWASAAN USIA PERKAWINAN DENGAN SIKAP REMAJA TERHADAP PERNIKAHAN DINI DI SMAN 1 KAMAL - Cindy Fatika Salsabila; Andriyanti Andriyanti; Nining Febriyana; Lilik Djuari (LPPM Universitas Abdurrab, 2025)
Background: Early marriage remains a significant challenge in developing countries, including Indonesia, which ranks fourth globally in child marriage cases. According to UNICEF (2023), there are 25.53 million child marriage cases in Indonesia. In 2022, the rate of early marriage in Bangkalan, Madura, continued to show an increasing trend, with an annual rise of 1.71%. The Marriage Age Maturity Program (PUP) aims to increase the minimum age of marriage to 21 years for women and 25 years for men. Objective: This study aims to examine the relationship between knowledge of marriage maturity and adolescent attitudes toward early marriage. Methods: This research uses a quantitative method with a cross-sectional design. The population consisted of 10th- and 11th-grade students at SMAN 1 Kamal, with a sample size of 183 respondents selected through cluster random sampling. The independent variable is knowledge of marriage maturity, while the dependent variable is adolescents' attitudes toward early marriage. A questionnaire was used as the instrument, and data analysis was performed using the Spearman rank test. Results: The study shows that most respondents (72.7%) have good knowledge about marriage maturity. Respondents with good knowledge tend to have a positive attitude or do not support early marriage (90%). The Spearman rank test revealed a p-value of <0.001 (<0.005), indicating a significant relationship between knowledge of marriage age maturity and adolescents' attitudes toward early marriage, with a low correlation level (r = 0.312). Recommendations: It is recommended that schools, particularly counseling services, conduct educational sessions on the importance of marriage age maturity to enhance adolescents' knowledge and prevent early marriage.